A compact proximity‐fed 2.4 GHz monostatic antenna with wide‐band SIC characteristics for in‐band full duplex applications. Issue 3 (11th December 2019) - Nawaz, Haq; Niazi, Ahmad U.
Abstract: This article presents a dual polarized, proximity‐fed monostatic patch antenna (single radiator for both transmit and receive modes) with improved interport isolation for 2.4 GHz in‐band full duplex (IBFD) applications. The proximity‐fed radiating patch offers comparatively wider impedance bandwidth for presented design. Very nice self‐interference cancelation (SIC) levels for intended impedance bandwidth have been achieved through differential receive (Rx ) mode configuration. The differential Rx mode based on 180° ring hybrid coupler acts as a signal inversion mechanism for effective suppression or cancelation of in‐band self‐interference (SI) that is, the leakage from transmit port. The implemented prototype of proposed antenna achieves ≥87 dB peak isolation for dual polarized IBFD operation. Moreover, the recorded interport isolation for validation model ≥60 dB within 10 dB‐return loss bandwidth of 90 MHz (2.36‐2.45 GHz). The measured radiation characteristics of implemented antenna demonstrate nice gain and low cross‐polarization levels for both transmit (Tx ) and receive (Rx ) modes. The dimensions of implemented antenna are 70 × 75 × 4.8 mm 3 . The novelty of this work is wide‐band SIC performance for monostatic antenna configuration with compact structure of presented design.